2016
DOI: 10.5603/dk.2015.0030
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life among patients with type 2 diabetes after insulin therapy introduction: A prospective study

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 13 publications
3
5
0
Order By: Relevance
“…These findings are corroborated by most studies on the QoL of women with hyperglycemia in pregnancy [11,13,14,28] and on QoL of non-pregnant diabetic patients [12,14,31]. Similar results were reported in studies on type 2 diabetes patients [24] and on pregnant women in Austria [35], though in these cases, poorer QoL was only found at the beginning of insulin therapy. The authors emphasize that the increase in reported QoL in the subsequent months of insulin therapy is associated with education provided to the patients, which reduces their fear of injections and concerns about the insulin administration technique.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These findings are corroborated by most studies on the QoL of women with hyperglycemia in pregnancy [11,13,14,28] and on QoL of non-pregnant diabetic patients [12,14,31]. Similar results were reported in studies on type 2 diabetes patients [24] and on pregnant women in Austria [35], though in these cases, poorer QoL was only found at the beginning of insulin therapy. The authors emphasize that the increase in reported QoL in the subsequent months of insulin therapy is associated with education provided to the patients, which reduces their fear of injections and concerns about the insulin administration technique.…”
Section: Discussionsupporting
confidence: 85%
“…The QoL of these women may be adversely affected by the resulting changes in mood and perceived health, and a partial loss of control over one's own body [11,14,22]. Due to the continuously growing interest in patients' QoL during illness and treatment, numerous studies have been published on the adverse impact of such conditions as type 1 or type 2 diabetes on QoL in adults and children [23][24][25][26]. However, research on the impact of hyperglycemia on the QoL of women during pregnancy is still lacking [11,14,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…These ndings are corroborated by most studies on the QoL of women with hyperglycemia in pregnancy [11,13,14,27] and on QoL of non-pregnant diabetic patients [12,30,34]. Similar results were reported in studies on type 2 diabetes patients [23] and on pregnant women in Austria [35], though in these cases, poorer QoL was only found at the beginning of insulin therapy. The authors emphasize that the increase in reported QoL in the subsequent months of insulin therapy is associated with education provided to the patients, which reduces their fear of injections and concerns about the insulin administration technique.…”
Section: Discussionsupporting
confidence: 78%
“…Due to the continuously growing interest in patients' QoL during illness and treatment, numerous studies have been published on the adverse impact of such conditions as type 1 or type 2 diabetes on QoL in adults and children [22][23][24][25]. However, research on the impact of hyperglycemia on the QoL of women during pregnancy is still lacking [11,14,[26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the continuously growing interest in patients' QoL during illness and treatment, numerous studies have been published on the adverse impact of such conditions as type 1 or type 2 diabetes on QoL in adults and children [23][24][25][26]. However, research on the impact of hyperglycemia on the QoL of women during pregnancy is still lacking [11,14,[27][28][29].…”
Section: Discussionmentioning
confidence: 99%